Posterior Midline Activation during Symptom Provocation in Acute Stress Disorder: An fMRI Study - Cwik, Jan C.; Sartory, Gudrun; Schürholt, Benjamin; Knuppertz, Helge; Seitz, Rüdiger J. (Frontiers in Psychiatry, 2014)
Functional imaging studies of patients with Posttraumatic Stress Disorder showed wide-spread activation of mid-line cortical areas during symptom provocation i.e., exposure to trauma-related cues. The present study aimed at investigating neural activation during exposure to trauma-related pictures in patients with Acute Stress Disorder (ASD) shortly after the traumatic event. Nineteen ASD patients and 19 healthy control participants were presented with individualized pictures of the traumatic event and emotionally neutral control pictures during the acquisition of whole-brain data with a 3-T fMRI scanner. Compared to the control group and to control pictures, ASD patients showed significant activation in mid-line cortical areas in response to trauma-related pictures including precuneus, cuneus, postcentral gyrus and pre-supplementary motor area. The results suggest that the trauma-related pictures evoke emotionally salient self-referential processing in ASD patients.